Metabolomics reveals alterations in gut-derived uremic toxins and tryptophan metabolism in feline chronic kidney disease - Laurens Van Mulders; Ellen Vanden Broecke; Ellen De Paepe; Femke Mortier; Lynn Vanhaecke; Sylvie Daminet (Veterinary Quarterly)
Chronic Kidney Disease (CKD) is one of the most common conditions affecting felines, yet the metabolic alterations underlying its pathophysiology remain poorly understood, hindering progress in identifying biomarkers and therapeutic targets. This study aimed to provide a comprehensive view of metabolic changes in feline CKD across conserved biochemical pathways and evaluate their progression throughout the disease continuum. Using a multi-biomatrix high-throughput metabolomics approach, serum and urine samples from CKD-affected cats (n = 94) and healthy controls (n = 84) were analyzed with ultra-high-performance liquid chromatography-high-resolution mass spectrometry. Significant disruptions were detected in tryptophan (indole, kynurenine, serotonin), tyrosine, and carnitine metabolism, as well as in the urea cycle. Circulating gut-derived uremic toxins, including indoxyl-sulfate, p-cresyl-sulfate, and trimethylamine-N-oxide, were markedly increased, primarily due to impaired renal excretion. However, alternative mechanisms, such as enhanced bacterial formation from dietary precursors like tryptophan, tyrosine, carnitine, and betaine, could not be ruled out. Overall, the findings suggest that metabolic disturbances in feline CKD are largely driven by the accumulation of gut-derived uremic toxins derived from precursors highly abundant in the feline diet. These insights may link the strict carnivorous nature of felines to CKD pathophysiology and highlight potential avenues for studying preventive or therapeutic interventions.